Trajectories of mindfulness, flow experience, and stress during an online-based MBSR program: the moderating role of emotional exhaustion - Hohnemann, Charlotte; Engel, Florian; Peifer, Corinna; Diestel, Stefan (Frontiers in Psychology, 2024)
Introduction Despite numerous papers focusing on mindfulness at work, our knowledge about how flow experience and stress as indicators of optimal functioning and wellbeing at work evolve over time during the common mindfulness-based stress reduction (MBSR) program remains limited. Drawing from the transactional model of flow and stress, we argue that a build-up of mindfulness over the training duration not only leads to a decrease in stress but also an increase in flow experience. Thereby, we examine the moderating role of emotional exhaustion amplifying the beneficial effects of mindfulness. Methods In a quasi-experimental study, 91 participants completed weekly questionnaires over the course of 8 weeks. Forty six participants in the experimental group took part in the MBSR program, while 45 participants were part of an inactive control group. Results Mindfulness and flow showed a significant linear increase over time, whereas stress exhibited a linear decrease. Those who participated in the MBSR training reported an increase in mindfulness that positively and negatively predicted the trajectories of flow and stress, respectively. Emotional exhaustion amplified the effects of the trajectory of mindfulness on the trajectories of flow and stress. Discussion These findings suggest that mindfulness can not only reduce stress but can also foster the autotelic experience of flow, especially for chronically depleted individuals. However, more research is necessary to replicate these results and address the limitations of the current study, including the quasi-experimental design, the use of self-report measures, as well as the dropout during the study period.